Analisis Implementasi Pengelolaan Dana Desa Menggunakan Aplikasi Siskeudes Desa Banyuanyar - Angela Ayu Wilma; Aprina Nugrahesthy Sulistya Hapsari (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2019)
Abstract. This research purpose to analyze the stages of village financial management Permendagri 113 of 2014 with the stages of village fund management by the application of Siskeudes in the Village of Banyuanyar Boyolali. This research is a qualitative descriptive study by observe at the phenomenon of the many cases of corruption about village funds. Data acquired by interviews and documentation. Qualitative analysis method used are data reduction, triangulation, data presentation and conclusion. The results and discussion of this research indicate that the stages of village financial management Permendagri 113 of 2014 with the stages of village funds management starting from the stages of planning, implementation, administration, reporting and accountability through the application of Siskeudes (Version V1.2.RI.0.6) in Banyuanyar is corresponding. Although there are differences in the stages of accountability, that do not process accountability reports by the application of Siskeudes, but only to complete the attachments needed as evidence in reporting accountability, but does not affect the process of village fund management Banyuanyar. Application of Siskeudes can be monitoring of village financial management, seen from all input of village fund management in Banyuanyar by the application of Siskeudes online by information on place, time and date in real time and directly connected with Boyolali Regency server.